1999
DOI: 10.1002/hep.510300513
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning protects the mouse liver by inhibition of apoptosis through a caspase-dependent pathway

Abstract: A short period of ischemia and reperfusion, called ischemic preconditioning, protects various tissues against subsequent sustained ischemic insults. We previously showed that apoptosis of hepatocytes and sinusoidal endothelial cells is a critical mechanism of injury in the ischemic liver. Because caspases, calpains, and Bcl-2 have a pivotal role in the regulation of apoptosis, we hypothesized that ischemic preconditioning protects by inhibition of apoptosis through down-regulation of caspase and calpain activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
192
2
15

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(224 citation statements)
references
References 72 publications
15
192
2
15
Order By: Relevance
“…1F-G) (n ϭ 7 each group), as shown in similar I/R models. 21 Mortality was not observed in this model of left lobar I/R. In conclusion, this partial I/R model induces hepatic oxidative stress and tissue injury in a background of stable hemodynamic parameters.…”
Section: Validation Of a Standardized Murine Model Ofmentioning
confidence: 64%
See 3 more Smart Citations
“…1F-G) (n ϭ 7 each group), as shown in similar I/R models. 21 Mortality was not observed in this model of left lobar I/R. In conclusion, this partial I/R model induces hepatic oxidative stress and tissue injury in a background of stable hemodynamic parameters.…”
Section: Validation Of a Standardized Murine Model Ofmentioning
confidence: 64%
“…Partial hepatic I/R was induced by occluding the vascular inflow of the left lateral liver lobe for 45 minutes, corresponding to approximately 40% of the liver mass. 21 All surgical procedures were performed under inhalation anesthesia with a 1.5% to 2% isoflurane/O 2 mixture using a mask. Buprenorfine (3 g/mouse) was administered intramuscularly before surgery to provide sufficient intraoperative and postoperative analgesia.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported that satraplatin treatment induces the accumulation of apoptotic cells even in the p53-null model, thus overcoming chemoresistance by a p53-independent mechanism [14] . Generally, the protection of cells against apoptosis requires the down-regulation of proapoptotic activities or the up-regulation of anti-apoptotic mechanisms [23] . The Bcl-2 family is an important regulator of cellular apoptosis [24] .…”
Section: Discussionmentioning
confidence: 99%